Dataset for gait analysis and assessment of fall risk for older adults - Caicedo, Pablo E.; Rengifo, Carlos F.; Rodriguez, Luis E.; Sierra, Wilson A.; Gómez, Maria C. (Elsevier, 2020)
This article presents a five-part dataset for human gait analysis in a healthy older adult population (37 women and seven men; age 69.98 ± 8.57 years, body mass index 27.71 ± 4.57). Part 1 compromises demographic data for the 44 participants, along with the results of the Short Physical Performance Battery (SPPB) motor function test and the MiniMental State Examination (MMSE). We used the MMSE to ensure the participants could understand the experimental protocol instructions. Part 2 presents the anthropometric measurements of the participants. Part 3 shows the results for each item of the Gait component of the Performance Oriented Mobility Assessment (POMA-G). Part 4 contains five files per participant, storing motion-capture data for the lower limb in the Coordinate 3D (C3D) format. These files were generated using a Vicon motion analysis system, consisting of 24 reflective markers and seven cameras (Vantage V5) sampled at 100 Hz. Part 5 contains 26 gait parameters for each C3D file obtained using Nexus 2.9.3. The dataset is available in a Mendeley repository

Este artículo presenta un conjunto de datos de cinco partes para el análisis de la marcha humana en una población de adultos mayores sanos (37 mujeres y siete hombres; edad 69,98 ± 8,57 años, índice de masa corporal 27,71 ±4,57). La parte 1 compromete los datos demográficos de los 44 participantes, junto con los resultados de la prueba de función motora Short Physical Performance Battery (SPPB) y el MiniMental State Examination (MMSE). Usamos el MMSE para Asegúrese de que los participantes puedan comprender las instrucciones del protocolo experimental. La parte 2 presenta las medidas antropométricas de los participantes. La Parte 3 muestra los resultados de cada ítem del componente de Marcha de la Evaluación de Movilidad Orientada al Desempeño (POMA-G). La parte 4 contiene cinco archivos por participante, que almacenan datos de captura de movimiento. para el miembro inferior en el formato Coordinate 3D (C3D). Estos Los archivos se generaron utilizando un sistema de análisis de movimiento Vicon, que consta de 24 marcadores reflectantes y siete cámaras (Vantage V5) muestreadas a 100 Hz. La parte 5 contiene 26 parámetros de marcha para cada archivo C3D obtenido con Nexus 2.9.3. El El conjunto de datos está disponible en un repositorio de Mendeley.
Keywords: Caídas (Accidentes) en la vejez; Falls (Accidents) in old age; Locomoción humana; Human locomotion; Mecánica humana; Human mechanics; Ingeniería biomédica - Procesamiento de datos; Biomedical Engineering - Data Processing; Análisis de la marcha; Gait analysis; Evaluación del riesgo de caída; Fall risk assessment; Evaluación de movilidad orientada al rendimiento; Performance oriented mobility assessment; POMA; Batería de rendimiento físico corto; Short physical performance battery; SPPB; Parámetros de marcha; Gait parameters; Prueba de función motora; Motor function test